ERNESTO ELIGIO TABÍO PALMA: PILLAR OF CUBAN ARCHAEOLOGY AT THE DAWN OF REVOLUTION - Hernández de Lara, Odlanyer (2013)
The first years of the Cuban Revolution were of great importance for the development of archaeology in Cuba. The new institutional structure and the ideological guidelines that began to be implemented led to the creation of the Academy of Sciences of Cuba and, within it, the Department of Anthropology, directed by the Cuban investigator Ernesto Eligio Tabío Palma, who at the time came back from a stay in Peru. The meaning of Tabío’s great work in the institutional organization of Cuban archaeology, as well as his influence on the structural guidelines of the discipline, whether in theory or in praxis, have given impulse to this approachment to some aspects of his life, his first archaeological explorations before he left for Peru, and, above all, his distinguished participation in the post-revolutionary stage, highlighting some aspects of his life work that, beyond its having been recognized or not by others, also have influenced some tendencies of Latin American archaeological thought.